Teacher’s Perseptions toward Electronic Student Worksheet Based on Yellow Well Water Purification Project to Improve Students’ Critical Thinking Skills - Elsa Pramudya Wardani; Chansyanah Diawati; Noor Fadiawati (Postgraduate, University of Mataram, 2024)
The objective of this research is to investigate the perceptions of science teachers towards e-worksheet based on the yellow well water purification project to improve students' critical thinking skills. The method used in this research is mixed methods with Explanatory Sequential Design. The data was collected through a questionnaire, then analyzed using descriptive analysis. The questionnaires were distributed to 13 science teacher respondents and 176 junior high school students in Susunan Baru sub-district area. The research results show that 69% of teachers have not used project-based electronic worksheet; based on student questionnaire responses, 72% of teachers have given project assignments to solve problems, but these projects are not based on real problems in the environment. The environmental problem that occurs in Susunan Baru sub-district area is the problem of the quality of well water being polluted by contaminants, causing the water to be yellow and smelly. The current worksheet has not completely train students' critical thinking skills because they are not based on real problems. Based on the research results, it can be concluded that e-worksheet based on the yellow well water purification project is needed to improve students' critical thinking skills.